Proteomic profiling of TGFBI‐null mouse corneas reveals only minor changes in matrix composition supportive of TGFBI knockdown as therapy against TGFBI‐linked corneal dystrophies. (23rd November 2017) - Poulsen, Ebbe Toftgaard; Runager, Kasper; Nielsen, Nadia Sukusu; Lukassen, Marie V.; Thomsen, Karen; Snider, Paige; Simmons, Olga; Vorum, Henrik; Conway, Simon J.; Enghild, Jan J.
Abstract : TGFBIp is a constituent of the extracellular matrix in many human tissues including the cornea, where it is one of the most abundant proteins expressed. TGFBIp interacts with Type I, II, IV, VI, and XII collagens as well as several members of the integrin family, suggesting it plays an important role in maintaining structural integrity and possibly corneal transparency as well. Significantly, more than 60 point mutations within the TGFBI gene have been reported to result in aberrant TGFBIp folding and aggregation in the cornea, resulting in severe visual impairment and blindness. Several studies have focused on targeting TGFBIp in the cornea as a therapeutic approach to treat TGFBI ‐linked corneal dystrophies, but the effect of this approach on corneal homeostasis and matrix integrity remained unknown. In the current study, we evaluated the histological and proteomic profiles of corneas from TGFBI‐ deficient mice as well as potential redundant functions of the paralogous protein POSTN. The absence of TGFBIp in mouse corneas did not grossly affect the collagen scaffold, and POSTN is unable to compensate for loss of TGFBIp. Proteomic comparison of wild‐type and TGFBI −/− mice revealed 11 proteins were differentially regulated, including Type VI and XII collagens. However, as these alterations did not manifest at the macroscopic and behavioral levels, these data support partial or complete TGFBI knockdown as a potential therapy against TGFBI ‐linked corneal dystrophies. Lastly, in situ hybridization verified TGFBI mRNA in the epithelial cells but not in other cell types, supportive of a therapy directed specifically at this lineage. Abstract : TGFBIp is a major constituent of the human cornea and is involved in the development of TGFBI ‐linked corneal dystrophy. The corneal proteome of TGFBIp knockout mice showed only minor changes and no apparent alterations of the ultrastructure. The data support TGFBI gene suppression as a potential therapy to TGFBI ‐linked corneal dystrophies.